2001
DOI: 10.1046/j.1469-7580.2001.19820153.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a hypermineralised calcified fibrocartilage on the human femoral neck and lesser trochanter

Abstract: Femoral neck fractures are a major cause of morbidity and mortality in elderly humans. In addition to the age-related loss of cancellous bone, changes to the microstructure and morphology of the metaphyseal cortex may be a contributing factor in osteoporotic hip fractures. Recent investigations have identified a hypermineralised tissue on the neck of the femur and trochanteric region that increases in fractional area with advancing age in both males (Boyce & Bloebaum, 1993) and females (Vajda & Bloebau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 25 publications
3
36
2
Order By: Relevance
“…This general structure has been shown to exist in numerous species, including human (Cooper and Misol, 1970;Benjamin et al, 1986;Evans et al, 1991;Shea et al, 2001b), rat Bland and Ashhurst, 1997;Benjamin et al, 2000), rabbit Clark and Stechschulte, 1998), dog (Clark and Stechschulte, 1998), and sheep (Clark and Stechschulte, 1998). However, this is the first investigation to compare the structure of the tendon insertions of the greater trochanter between different species.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This general structure has been shown to exist in numerous species, including human (Cooper and Misol, 1970;Benjamin et al, 1986;Evans et al, 1991;Shea et al, 2001b), rat Bland and Ashhurst, 1997;Benjamin et al, 2000), rabbit Clark and Stechschulte, 1998), dog (Clark and Stechschulte, 1998), and sheep (Clark and Stechschulte, 1998). However, this is the first investigation to compare the structure of the tendon insertions of the greater trochanter between different species.…”
Section: Discussionmentioning
confidence: 89%
“…
ABSTRACTResearch has shown that there is a dramatic increase in the fractional area of calcified fibrocartilage from tendon and capsular insertions on the human femoral neck Shea et al, 2001b). Additional information regarding the properties of the proximal femur's cortical shell, gained from the use of an animal model, may result in a better understanding of elderly hip fracture since the cortical shell is a significant contributor to the strength of the proximal femur.
…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these studies there are some opposed observations claiming that the femoral neck periosteal covering exists. 8,34,98,112 Periosteal cellularity at the femoral neck is significantly lower than in the diaphyseal region even in young adults. Twenty percent of the femoral neck surface has cellular periosteum which suggests that anabolic osteogenic therapies may be effective in strengthening this clinically relevant site.…”
Section: Microscopic Featuresmentioning
confidence: 99%